Patient-Derived Microphysiological Systems for Precision Medicine - Ko, Jihoon; Song, Jiyoung; Choi, Nakwon; Kim, Hong Nam (Wiley-Blackwell, 2024)
Patient-derived microphysiological systems (P-MPS) have emerged as powerful tools in precision medicine that provide valuable insight into individual patient characteristics. This review discusses the development of P-MPS as an integration of patient-derived samples, including patient-derived cells, organoids, and induced pluripotent stem cells, into well-defined MPSs. Emphasizing the necessity of P-MPS development, its significance as a nonclinical assessment approach that bridges the gap between traditional in vitro models and clinical outcomes is highlighted. Additionally, guidance is provided for engineering approaches to develop microfluidic devices and high-content analysis for P-MPSs, enabling high biological relevance and high-throughput experimentation. The practical implications of the P-MPS are further examined by exploring the clinically relevant outcomes obtained from various types of patient-derived samples. The construction and analysis of these diverse samples within the P-MPS have resulted in physiologically relevant data, paving the way for the development of personalized treatment strategies. This study describes the significance of the P-MPS in precision medicine, as well as its unique capacity to offer valuable insights into individual patient characteristics. Microphysiological systems now integrate patient-derived samples, functioning as physiologically relevant avatars for high-throughput assays. This evolution addresses an unmet clinical need for a patient-centered nonclinical assessment platform, steering toward more precise and personalized approaches in medical research and drug development.image